Allergy to oxidized limonene and linalool is frequent in the U.K. (1st August 2014) - Audrain, H.; Kenward, C.; Lovell, C.R.; Green, C.; Ormerod, A.D.; Sansom, J.; Chowdhury, M.M.U.; Cooper, S.M.; Johnston, G.A.; Wilkinson, M.; King, C.; Stone, N.; et al.
Summary: Background: The oxidized forms of the fragrance terpenes limonene and linalool are known to cause allergic contact dermatitis. Significant rates of contact allergy to these fragrances have been reported in European studies and in a recent worldwide study. Patch testing to oxidized terpenes is not routinely carried out either in the U.K. or in other centres internationally. Objectives: To investigate the prevalence of contact allergy to oxidized limonene and linalool in the U.K. Methods: Between 1 August 2011 and 31 December 2012, 4731 consecutive patients in 13 U.K. dermatology departments were tested for hydroperoxides of limonene 0·3% pet., hydroperoxides of linalool 1·0% pet., stabilized limonene 10·0% pet. and stabilized linalool 10·0% pet. Doubtful (?+) and equivocal (±) reactions were grouped together as irritant reactions. Results: Two hundred and thirty‐seven patients (5·0%) had a positive patch test reaction to hydroperoxides of limonene 0·3% pet. and 281 (5·9%) to hydroperoxides of linalool 1·0% pet. Irritant reactions to one or both oxidized terpenes were found in 242 patients (7·3%). Eleven patients (0·2%) had a positive patch test reaction to the stabilized terpenes alone. Conclusions: This large, multicentre U.K. audit shows a significant rate of allergy to the hydroperoxides of limonene and linalool plus a high rate of irritant reactions. Testing to the oxidized forms alone captures the majority (97·0%; 411 of 422) of positive reactions; testing to nonoxidized terpenes appears to be less useful. We recommend that the hydroperoxides of limonene and linalool be added to an extended baseline patch test series.